Functional features of the heart in cyclists - I.N. Medvedev,; O.A. Razzhivin,; A.V. Dorontsev,; V.V. Belyaev, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the effect of training loads on the functional parameters of the heart of cyclists. Methods and structure of the study. The observation was made on 18 trained young cyclists with at least three years of sports training experience. The control group included 22 clinically healthy young men who did not go in for sports. Echocardiography was performed on the SSD-80 Aloka device (Japan). Results and conclusions. Experienced cyclists have left ventricular myocardial hypertrophy. It was manifested by an increase in the thickness of its walls and its mass while maintaining the optimum of its overall size and the size of its cavity. Well-trained cyclists are characterized by a high rate of relaxation of the heart muscle. It is clear that regular cycling increases the physical capabilities of a person, trains his heart, while maintaining the optimum of general hemodynamics.